Gamification in logistics and supply chain education: Extending active learning - Wood, Lincoln; Reiners, Torsten (IADIS Press, 2012)
Engagement with users involved in an activity has become increasingly important, particularly in Higher Education. We review the concept of gamification and outline several existing applications. These incorporate game elements into existing systems and tasks in a way that increases user engagement in the process. Current approaches in logistics and supply chain education are discussed in relation to active learning. We develop a framework that combines several gamification elements that can be relatively easily incorporated into existing approaches and learning management systems (LMSs) in ways that aims to increase engagement and extend active learning. This framework and the relationship between the elements provide fertile ground for further research.